A More Plausible Collapsing Principle. (4th September 2018) - Andersson, Henrik; Herlitz, Anders
Abstract: In 1997 John Broome presented the Collapsing Argument that was meant to establish that non‐conventional comparative relations (e.g., "parity, " "imprecise equality, " "incommensurability") cannot exist. Broome's argument has faced a lot of scrutiny and a certain type of counterexample has been used to undermine it. Most of the counterexamples focus on the Collapsing Principle which plays a central role in Broome's argument. In this article we will take a closer look at the most common type of counterexample and propose how to adjust the Collapsing Principle in order to avoid objections based on these counterexamples. We argue that a weaker version of the Collapsing Principle is not susceptible to the classical counterexamples. Furthermore, after an explorative discussion about the intuitions behind the original principle, we show that this weaker formulation is at least as intuitive as the principle suggested by Broome.